Ethnic Bargaining : The Paradox of Minority Empowerment - Jenne, Erin K. (Book collections on Project MUSE., 2007)
"Ethnic Bargaining introduces a theory of minority politics that blends comparative analysis and field research in the postcommunist countries of East Central Europe with insights from rational choice. Erin K. Jenne finds that claims by ethnic minorities have become more frequent since 1945 even though nation-states have been on the whole more responsive to groups than in earlier periods. Minorities that perceive an increase in their bargaining power tend to radicalize their demands, she argues from affirmative action to regional autonomy to secession, in an effort to attract ever greater concessions from the central government." "Jenne uses a rationalist theory of bargaining to examine the dynamics of ethnic cleavage in the cases of the Sudeten Germans in interwar Czechoslovakia; Slovaks and Moravians in postcommunist Czechoslovakia; the Hungarians in Romania, Slovakia, and Vojvodina; and the Albanians in Kosovo. Throughout, she challenges the conventional wisdom that partisan intervention is an effective mechanism for protecting minorities and preventing or resolving internal conflict."--Jacket